Comparative Electoral Management Performance, Networks and Instruments (Taylor & Francis, 2020)
This book offers the first comparative monograph on the management of elections. The book defines electoral management as a new, inter-disciplinary area and advances a realist sociological approach to study it. A series of new, original frameworks are introduced, including the PROSeS framework, which can be used by academics and practitioners around the world to evaluate electoral management quality. A networked governance approach is also introduced to understand the full range of collaborative actors involved in delivering elections, including civil society and the international community. Finally, the book evaluates some of the policy instruments used to improve the integrity of elections, including voter registration reform, training and the funding of elections. Extensive mixed methods are used throughout including thematic analysis of interviews, (auto-)ethnography, comparative historical analysis and, cross-national and national surveys of electoral officials. This text will be of key interest to scholars, students and practitioners interested and involved in electoral integrity and elections, and more broadly to comparative politics, public administration, international relations and democracy studies.
English
Keywords: elections; management; thema EDItEUR::J Society and Social Sciences::JP Politics and government